Development of a novel lateral resistance measurement penetrometer for pipe–soil interaction centrifuge model test - Yu Zhang; Zhongtao Wang; Huafu Pei (International Journal of Distributed Sensor Networks)
Offshore pipelines are exposed to potential submarine landslides. It is difficult to measure the impact forces exerted on a pipeline induced by submarine landslides because the upper seabed is very soft and an impact angle exists in practice. Current laboratory experiments are limited on measuring the normal force exerted on pipeline by the slides. This article describes the feasibility and performance of a novel penetrometer, which is designed to measure impact forces of submarine landslides on offshore pipeline including both the normal and frictional forces from variable impact angle in centrifuge test, termed as the lateral resistance measurement penetrometer. The calibration procedure for this particular version is illustrated in detail and the reliability and feasibility of the lateral resistance measurement penetrometer are preliminarily confirmed by an experimental study. Pipe–soil interaction centrifuge tests were subsequently performed on a normally consolidated kaolin sample with 40 g level conducted in Dalian University of Technology drum centrifuge to investigate the effect of incident angles on the impact forces exerted by submarine landslides on a pipeline. The impact forces deduced from the lateral resistance measurement penetrometer are analysed in comparison with published results. The lateral resistance measurement penetrometer is a potentially valuable device to measure the interaction force between submarine landslides and offshore pipeline, cables and other subsea facilities in small-scale centrifuge models.